Prebavne lipaze in njihov pomen pri aplikaciji zdravil - Rede, Katarina (Farmacevtski vestnik, 2022)
Digestive enzymes play an important role in food breakdown and they are also frequently involved in oral drug delivery. One of digestive enzyme groups is lipases, which catalyze the hydrolysis of lipids, resulting in the formation of digestion products that can be absorbed. The most important digestive lipases in humans are gastric and pancreatic lipases. Gastric lipase is an acid-stable enzyme, which is secreted from gastric mucosa. It initiates lipid digestion. Pancreatic lipase, which contributes to lipolysis to the greatest extent, is secreted from the pancreas into the duodenum and continues lipid digestion. The process of lipid digestion can also influence the bioavailability of a drug incorporated into lipid-based drug delivery systems, as components of these systems can be digested by lipases, and it can also affect oral lipid prodrugs. Therefore, knowledge about lipase activity is an important factor in the development of these drug delivery systems and their biopharmaceutical evaluation.
Keywords: Dostavni sistemi; Encimi; Lipidi; lipidni dostavni sistemi; pankreasna lipaza; prebava; Zdravilne učinkovine; želodčna lipaza